Two-phase microalgae cultivation for RAS water remediation and high-value biomass production - Villanova, Valeria; Roques, Jonathan Armand Charles; Forghani, Bita; Shaikh, Kashif Mohd; Undeland, Ingrid; Spetea, Cornelia (Frontiers in Plant Science, 2023)
The overall goal of this study was to provide solutions to innovative microalgae-based technology for wastewater remediation in a cold-water recirculating marine aquaculture system (RAS). This is based on the novel concept of integrated aquaculture systems in which fish nutrient-rich rearing water will be used for microalgae cultivation. The produced biomass can be used as fish feed, while the cleaned water can be reused, to create a highly eco-sustainable circular economy. Here, we tested three microalgae species Nannochloropis granulata (Ng), Phaeodactylum tricornutum (Pt), and Chlorella sp (Csp) for their ability to remove nitrogen and phosphate from the RAS wastewater and simultaneously produce high-value biomass, i.e., containing amino acids (AA), carotenoids, and polyunsaturated fatty acids (PUFAs). A high yield and value of biomass were achieved for all species in a two-phase cultivation strategy: i) a first phase using a medium optimized for best growth (f/2 14x, control); ii) a second “stress” phase using the RAS wastewater to enhance the production of high-value metabolites. Ng and Pt performed best in terms of biomass yield (i.e., 5-6 g of dry weight, DW, L-1) and efficient cleaning of the RAS wastewater from nitrite, nitrate, and phosphate (i.e., 100% removal). Csp produced about 3 g L-1 of DW and reduced efficiently only nitrate, and phosphate (i.e., about 76% and 100% removal, respectively). The biomass of all strains was rich in protein (30-40 % of DW) containing all the essential AA except Methionine. The biomass of all three species was also rich in PUFAs.. Finally, all tested species are excellent sources of antioxidant carotenoids, including fucoxanthin (Pt), lutein (Ng and Csp) and β-carotene (Csp). All tested species in our novel two-phase cultivation strategy thus showed great potential to treat marine RAS wastewater and provide sustainable alternatives to animal and plant proteins with extra added values.